Chondrolysis of the Ankle Joint following Ankle Arthroscopy and Microfracture of the Osteochondral Lesion of the Talar Dome - Tsz Lung Choi; Tun Hing Lui (Case Reports in Orthopedics)
Chondrolysis of the ankle is a very rare condition. We report a case of chondrolysis of the ankle following ankle arthroscopy and microfracture of the osteochondral lesion of the talar dome. The patient’s symptoms were relieved after articulated distraction arthroplasty.